Investigation of the Effectiveness of Monoethanolamides as Low Sulfur Marine Fuel Lubricity Additives. (2018) - Anastopoulos, G.; Schinas, P.; Zannikou, Y.; Karonis, D.; Zannikos, F.; Lois, E.
Abstract: In this study, six mixtures of monoethanolamides that were synthesized from various vegetable oils (Sunflower oil, Soybean Oil, Cotton Seed Oil, Olive oil, Tobacco seed oil, Used frying oil) were used as lubricating additives on a low sulfur Marine Gas Oil (MGO). All tribological measurements were carried out by using the HFRR test procedure, according to ISO 12156-1. The obtained wear results showed that all mixtures of monoethanolamides used provide satisfactory a mean wear scar diameter (WS 1.4) of less than 520 μm, at concentration levels of 80 - 140 ppm. The concentrations below 80 ppm had no effect on the fuel lubricity.